MESOWEAR AND PALEODIETS OF MIDDLE MIOCENE MAMMALS FROM CHABBAR SYEDAN, PUNJAB, PAKISTAN - M. K. Nawaz; K. Aftab2; M. A. Khan; S. G. Abbas; M. Asim; M. A. Babar; M. Hussain; M. Akhtar (Journal of Animal and Plant Sciences, 2021)
The paleodiets of seven mammalian species from Chabbar Syedan are analysed using dental mesowear. Mesowear results suggest that Miotragocerus gluten, Eotragus sp., Giraffokeryx punjabiensis, Giraffa priscilla, Dorcatherium minus had attrition dominant diet and fall within dietary spectra of browsers to occasional mixed feeders. Gazella sp. and Listriodonpentapotamiae had an intermediate attrition-abrasion wear signatures and were mixed feeders or browse dominated mixed feeders. The mesowear data of Chabbar Syedan mammals were compared with previous palaeodietary studies and it showed that the results are most closely in line with the previous studies. These results also indicate that during Middle Miocene of Chabbar Syedan, browsing mammals were dominant and ecological conditions were more favorable for browsers than to exclusive grazers.
Keywords: Mesowear; Miocene; Chinji; Mammals; Paleodiets; Siwaliks